Heat transfer modeling for supercritical methane flowing in rocket engine cooling channels. (22nd January 2015) - Pizzarelli, Marco; Nasuti, Francesco; Onofri, Marcello; Roncioni, Pietro; Votta, Raffaele; Battista, Francesco
Abstract: To investigate the methane behavior inside rocket engine cooling channels, a test article has been specifically designed by the Italian Aerospace Research Center. In this study, the expected wall and coolant behavior of this test article is analyzed by a three-dimensional conjugate heat transfer model. Different coolant pressure and surface roughness levels are considered in order to understand their influence on the heat transfer capability of the cooling system. Results show that heat transfer deterioration may occur in principle when methane is operated in near-critical condition. However, the resultant wall temperature peak reduces for increasing coolant pressure and for increasing surface roughness. Highlights: Numerical simulation of methane in supercritical pressure and subcritical to supercritical temperature. Fluid and structure thermal coupling. Asymmetrically heated channels of rectangular cross section. Supercritical-pressure methane may exhibit heat transfer deterioration. Heat transfer deterioration is mitigated increasing coolant pressure and/or surface roughness.